Meetings to fantasize and imagine: experience of literary literacy and shared reading of literature (Revista Contexto & Educação, 2026)
The Covid-19 pandemic produced a dystopian situation and generated challenges between 2020/2021. In the post-pandemic context, action research was carried out with production and qualitative analysis of data, which was guided by the search for an answer to the following problem: Is shared reading a tool capable of promoting literary literacy and contributing to the formation of child readers? The article aims to discuss shared reading as a pedagogical tool for literary literacy, providing conditions for the insertion of children in the world of written culture. Weekly meetings were held to read books with and for children from the 1st to 5th grade of school, which promoted powerful dialogues, spaces for sharing, imagining and meaning. The results indicate that shared reading mediations transformed the classroom into places-times of learning, capable of producing literary literacy and contributing to the formation of child readers.
Keywords: Literacy; Shared Reading; Literary Literacy; Learning to Read; Post-pandemic